NAVIGATING THE CONUNDRUM: ACUTE LIVER FAILURE IN HYPERTHYROIDISM AND THE TREATMENT DILEMMA - Salleh, Mohd Fauzan; Marzuki, Marisa Masera; Chia, Wei Zhi; Ali, Norhaliza Mohd; Chai, Shu Teng; Im, Jamie Teoh Hong (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hyperthyroidism is a complex endocrine disorder associated with various systemic manifestations. Liver dysfunction in hyperthyroidism is a relatively rare but potentially serious complication. We present a case of a patient with hyperthyroidism who initially received inadequate treatment and subsequently developed acute liver failure. The causative role of hyperthyroidism itself versus antithyroid medication-induced liver injury remains elusive, posing a therapeutic challenge. A comprehensive review of the patient’s medical records, laboratory findings, imaging studies, and clinical progress was undertaken. Additionally, relevant literature concerning liver dysfunction associated with hyperthyroidism and druginduced liver injury was explored. CASE Two months after initiating carbimazole therapy, a 42-yearold male with a history of hyperthyroidism presented with jaundice. Subsequent liver function tests indicated significant conjugated hyperbilirubinemia, accompanied by abnormalities in prothrombin time, development of hepatorenal syndrome, and encephalopathy. Imaging studies detected no structural abnormalities. Despite thorough evaluation, the exact cause of his liver failure remained elusive, posing challenges in distinguishing between exacerbation of hyperthyroidism and carbimazoleinduced hepatotoxicity. Close monitoring ensued, with consideration given to liver transplant if necessary. Discontinuation of carbimazole and initiation of Lugol’s iodine and cholestyramine led to clinical improvement. Radioactive iodine therapy was planned as the definitive treatment. CONCLUSION While acute liver failure in Graves’ disease is rare, its management poses significant hurdles. Despite cholestasis and liver dysfunction, meticulous methimazole administration can effectively control hyperthyroidism with careful monitoring. However, when the cause of liver injury remains elusive—whether from the disease itself or its treatment—crafting an appropriate management plan becomes particularly complex. A different treatment approach may be necessary to achieve euthyroid state, often necessitating definitive therapy in such cases.